Chiral Bora[1]ferrocenophanes: Syntheses, Mechanistic Insights, and Ring‐Opening Polymerizations. Issue 49 (15th October 2014) - Sadeh, Saeid; Bhattacharjee, Hridaynath; Khozeimeh Sarbisheh, Elaheh; Quail, J. Wilson; Müller, Jens
Abstract A series of new boron‐bridged [1]ferrocenophanes ([1]FCPs) was prepared by salt‐metathesis reactions between enantiomerically pure dilithioferrocenes and amino(dichloro)boranes (Et2NBCl2, iPr2NBCl2, or tBu(Me3Si)NBCl2). The dilithioferrocenes were prepared in situ by lithium–bromine exchange from the respective planar‐chiral dibromides (Sp, Sp)‐[1‐Br‐2‐(HR2C)H3C5]2Fe (R=Me or Et). In most of the cases, mixtures of the targeted [1]FCPs 4 and the unwanted 1, 1′‐bis(boryl)ferrocenes 5 were formed. The product ratio depends on the bulkiness of the amino group, the speed of addition of the amino(dichloro)borane, the alkyl group on Cp rings, and in particular on the reaction temperature. The formation of strained [1]FCPs is strongly favored by increased reaction temperatures. Secondly, CHEt2 groups at Cp rings favored the formation of the targeted [1]FCPs stronger than CHMe2 groups. These discoveries open up new possibilities to further suppress the formation of unwanted byproducts by a careful choice of the reaction temperature and through tailoring the bulkiness of CHR2 groups on ferrocene. Thermal ring‐opening polymerizations of selected boron‐bridged [1]FCPs gave metallopolymers with a Mw of 10 kDa (GPC).